DEVELOPMENT OF INTERACTIVE E-MODULES USING FLIP PDF PROFESSIONAL BASED ON A CONTEXTUAL APPROACH TO BUILDING FLAT SIDE SPACE MATERIALS - Wando Satria Parapat; Prihatin Ningsih Sagala (Indonesian Journal of Multidisciplinary Science, 2022)
The development of this learning media is carried out to produce contextual-based interactive e-modules with the help of a professional flip pdf application that meets the valid, practical, and effective categories. So that it is useful for students in improving understanding of the flat-sided geometry material, especially the cube and beam submaterial. The research instruments used were lesson plans, material validation sheets and e-module media, pretest and posttest, as well as student and teacher response questionnaires. After all instruments, lesson plans, and e-modules are in the valid category, then they are tested in small groups and in the field. The results showed that: (1) the E-Module was in the valid category in terms of material and media, namely (92.70% and 90.97%) with a very feasible category; (2) the E-Module has met the practical value of the responses of students and teachers, namely (87.05% and 87.5%) in the very practical category; (3) The E-Modul meets the criteria of being effective with the completeness of student learning outcomes reaching 90% of students who get a score of 75 and the achievement of each indicator/learning objective that exceeds 75% of the total students. Based on the analysis of the research results, the N-Gain was 0.72, so it was included in the high category providing the effectiveness of student learning outcomes.